Combination of Alanine and Glutathione as Targeting Ligands of Nanoparticles Enhances Cargo Delivery into the Cells of the Neurovascular Unit - Gergő Porkoláb; Mária Mészáros; András Tóth; Anikó Szecskó; András Harazin; Zsolt Szegletes; Györgyi Ferenc; András Blastyák; Lajos Mátés; Gábor Rákhely; Mária A. Deli; Szilvia Veszelka (MDPI AG, 2020)
Inefficient drug delivery across the blood-brain barrier (BBB) and into target cells in the brain hinders the treatment of neurological diseases. One strategy to increase the brain penetration of drugs is to use vesicular nanoparticles functionalized with multiple ligands of BBB transporters as vehicles. Once within the brain, however, drugs must also be able to reach their therapeutic targets in the different cell types. It is, therefore, favorable if such nanocarriers are designed that can deliver their cargo not only to brain endothelial cells, but to other cell types as well. Here, we show that alanine-glutathione dual-targeting of niosomes enhances the delivery of a large protein cargo into cultured cells of the neurovascular unit, namely brain endothelial cells, pericytes, astrocytes and neurons. Furthermore, using metabolic and endocytic inhibitors, we show that the cellular uptake of niosomes is energy-dependent and is partially mediated by endocytosis. Finally, we demonstate the ability of our targeted nanovesicles to deliver their cargo into astroglial cells after crossing the BBB in vitro. These data indicate that dual-labeling of nanoparticles with alanine and glutathione can potentially be exploited to deliver drugs, even biopharmacons, across the BBB and into multiple cell types in the brain.